Physical Relationships and Image at Roland Barthes - حميدوش, لينا (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
In this research, we dealt with various issues related to the physical relations and photography of Roland Barthes, who in turn dealt with the concept of photography, and the relations of images that emerge as readable and interpretable texts. As for this research, it talked particularly about the physical relationships as they appear in the image, so we discussed the pictorial body and the written body and the act of pleasure emphasized by Barthes, where the body is the body of pleasure in its erotic sense. Barthes did not talk about moral pleasure, but rather frankly speaking about bodily pleasure in the text and the image, which made us discuss the body as a photographic text, which led us to reveal the cases of the image and the physical relationships of the body itself. These relationships that often revealed the loss of identity, that is, the identity of the body and the presence of forgery, which prevents the viewer from recognizing the content of the image, even if this content is the viewer's own body, to end the search by talking about the narrated body and the narrator's body